OFDM PAPR reduction for image transmission using improved tone reservation - Ghanim, Zainab Noori; Omran, Buthaina M. (Institute of Advanced Engineering and Science, 2021)
High peak to average power ration (PAPR) in orthogonal frequency division multiplexing (OFDM) is an important problem, which increase the cost and complexity of high power amplifiers. One of the techniques used to reduce the PAPR in OFDM system is the tone reservation method (TR). In our work we propose a modified tone reservation method to decrease the PAPR with low complexity compared with the conventional TR method by process the high and low amplitudes at the same time. An image of size 128×128 is used as a source of data that transmitted using OFDM system. The proposed method decrease the PAPR by 2dB compared with conventional method with keeping the performance unchanged. The performance of the proposed method is tested with several numbers of subcarriers; we found that the PAPR is reduced as the number of subcarriers decreased.